دەروازەیەک بۆ تێگەشتن لە پارادایمەکانی توێژینەوە - مستەفا, پ.ی.د. عالیە فرج; حمەسعید, م. ی. ئارام تۆفیق (Sulaimani Journal for Humanities, 2023)
The lack of literature in Kurdish language on research paradigms in the field of social sciences creates complications for new researchers. This paper attempts to discuss some of the basic issues of social science research in order to provide a clear presentation for researchers in this field. The purpose of this paper is to provide a brief overview of the different research paradigms. Examines the philosophical underpinnings of three major paradigms: positivism, Interpretivism, and critical theory. The paper reviews the literature on research paradigms, identifies differences between the mentioned paradigms, and explains their ontological and epistemological positions. It also carefully defines and explores different research methodologies and methods. It emphasizes that we need to be careful in our choice of research paradigm and to design our research with a clear connection between the nature of the paradigm and the theoretical framework of research. The decision to choose a philosophical perspective for the study of a phenomenon is important to be guided by the demands and needs of a study rather than a rigid insistence on adhering to a particular philosophical perspective to the exclusion of others. It is important that researchers adopt an appropriate approach to the choice of research methods or combination of methods, but the choice of any research method should not be interpreted as indicative of an ontological or epistemological position, in the sense that the choice of research paradigm takes precedence.
Keywords: پارادایمی توێژینەوە پۆزیتیڤیزم شیکارگەرایی ڕەخنەیی بوونناسی مەعریفەناسی میتۆدناسی